2019
DOI: 10.1080/17461391.2019.1587520
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of disordered eating in elite female athletes in team sports in Greece

Abstract: The purpose of the study was to assess a) the prevalence of disordered eating (DE) in elite female team sports players compared to non-athletes and b) to compare DE prevalence in elite female players in basketball, volleyball and water polo. One hundred and seventy-five females were recruited (age 23.10 ± 5.4, BMI 21.85 ± 2.3 kg/m 2), 53 were elite basketball players, 42 were elite volleyball players, 34 were elite water polo players and 46 were non-athletes. Participants completed the Eating Disorders Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 61 publications
0
13
1
2
Order By: Relevance
“…Results were then analyzed using X 2 analysis. Weight-dependent sports (44.2%) had higher prevalence of DE than Endurance (12.8%) and Ball Game (16.7%) sports ( p < 0.001) Strong correlation between male weight-dependent sports and higher prevalence of DE Kampouri et al, 2019 [ 32 ] Greek elite female athletes mean age of 23.10 ( n = 129) and female non-athletes ( n = 46) Ball Sport vs Non-Athlete 53 Basketball 42 Volleyball 34 Water Polo 46 Non-athletes Athletes were administered the Eating Disorders Questionnaire (EDE-Q). Results about inter-sport difference were analyzed using ANOVA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Results were then analyzed using X 2 analysis. Weight-dependent sports (44.2%) had higher prevalence of DE than Endurance (12.8%) and Ball Game (16.7%) sports ( p < 0.001) Strong correlation between male weight-dependent sports and higher prevalence of DE Kampouri et al, 2019 [ 32 ] Greek elite female athletes mean age of 23.10 ( n = 129) and female non-athletes ( n = 46) Ball Sport vs Non-Athlete 53 Basketball 42 Volleyball 34 Water Polo 46 Non-athletes Athletes were administered the Eating Disorders Questionnaire (EDE-Q). Results about inter-sport difference were analyzed using ANOVA.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that, though useful, the lean grouping does not provide a complete picture when addressing DE risk. The rest of the significant positive findings were shown in weight-dependent [31], power [32], antigravitation [32], and the specific ball sport water polo [27]. These provide insight into the risk of more specific groupings and therefore the risk factors of DE in athletes, but due to lack of evidence nothing more definitive can be said about the sport type groupings at this time.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been suggested that athletes who compete in sports where it is advantageous to have a lower fat mass (e.g., cycling, gymnastics, swimming, and running,) are more likely to exhibit DE than athletes from other sports [ 13 ]. Perhaps as a result, there are far fewer studies examining the prevalence of DE in sports less associated with leanness, such as soccer, hockey, basketball, and rugby, typically referred to as team or intermittent sports [ 14 ]. Nonetheless, of the few studies conducted, it is clear that team-sport players are not necessarily immune to DE.…”
Section: Introductionmentioning
confidence: 99%